The “Abdominal Circulatory Pump”: An Auxiliary Heart during Exercise? - Uva, Barbara; Aliverti, Andrea; Bovio, Dario; Kayser, Bengt (Frontiers in Physiology, 2016)
Apart from its role as a flow generator for ventilation the diaphragm has a circulatory role. The cyclical abdominal pressure variations from its contractions cause swings in venous return from the splanchnic venous circulation. During exercise the action of the abdominal muscles may enhance this circulatory function of the diaphragm. Eleven healthy subjects (25±7yr, 70±11kg, 1.78±0.1m, 3F) performed plantar flexion exercise at ∼4 METs. Changes in body volume (ΔVb) and trunk volume (ΔVtr) were measured simultaneously by double body plethysmography. Volume of blood shifts between trunk and extremities (Vbs) was determined non-invasively as ΔVtr-ΔVb. Three types of breathing were studied: spontaneous (SE), rib cage (RCE, voluntary emphasized inspiratory rib cage breathing) and abdominal (ABE, voluntary active abdominal expiration breathing).. During SE and RCE blood was displaced from the extremities into the trunk (on average 0.16± 0.33L and 0.48±0.55L, p<0.05 SE vs RCE), while during ABE it was displaced from the trunk to the extremities (0.22±0.20L p<0.001, p<0.05 RCE and SE vs ABE respectively). At baseline, Vbs swings (maximum to minimum amplitude) were bimodal and averaged 0.13±0.08L. During exercise, Vbs swings consistently increased (0.42±0.34L, 0.40±0.26L, 0.46±0.21L, for SE, RCE and ABE respectively, all p<0.01 vs. baseline). It follows that during leg exercise significant bi-directional blood shifting occurs between the trunk and the extremities. The dynamics and partitioning of these blood shifts strongly depend on the relative predominance of the action of the diaphragm, the rib cage and the abdominal muscles. Depending on the partitioning between respiratory muscles for the act of breathing, the distribution of blood between trunk and extremities can vary by up to 1 L. We conclude that during exercise the abdominal muscles and the diaphragm might play a role of an ‘auxiliary heart’.